Evaluation of hepatic tumor portal perfusion using mesenteric angiography: A pilot study in 5 dogs. (18th December 2018) - Goode, Kelsey; Weisse, Chick; Berent, Allyson; Lamb, Ken
Abstract : Background: Mesenteric angiography is a sensitive method for visualizing portal perfusion in the dog. Objectives: To evaluate hepatic portal perfusion in dogs with incompletely resectable hepatic tumors using mesenteric angiography. Animals: Five client‐owned dogs with incompletely resectable hepatic tumors evaluated with mesenteric angiography. Methods: Retrospective case series. Electronic medical records at the Animal Medical Center were analyzed to identify dogs that underwent mesenteric portography to determine blood flow to nonresectable hepatic tumors and subsequently determine ideal routes for transarterial embolization, vascular stent placement, or both. The images obtained from mesenteric angiography were analyzed and compared to those obtained from computed tomography angiography. Results: Portography was accomplished using direct mesenteric venography in 3 dogs with hepatocellular carcinoma (HCC), cranial mesenteric arteriography in 1 dog with hepatic adenoma or well‐differentiated HCC, and via splenic arteriovenous fistula in 1 dog with diffuse hepatic hemangiosarcoma metastases. Mean pixel densities in areas of hepatic tumor growth identified statistically significant decreases in portal blood flow ( P = .02) compared to normal hepatic parenchyma. Conclusions and Clinical Importance: Initial findings indicate that the blood supply to large and metastatic hepatic tumors in dogs may correlate with that in humans, such that the majority of the tumor blood supply arises from the hepatic artery and not the portal vein. Differences in blood supply between normal hepatic parenchyma and hepatic tumors might be exploited by developing selective tumor therapies such as arterial embolization or chemoembolization that largely spare normal liver tissue. Further investigation is warranted.